Effect Of Progressive Muscle Relaxation Technique On Pain In Post Sectio caesarea - Andria Pragholapati (Jurnal Kesehatan dr. Soebandi, 2020)
The cause of AKI at delivery is the presence of complicating factors during labor. To save mather and baby during childbirth due to labor complicating factors, one of them is by performing section caesarea, the most frequent impact felt by klien post section caesarea is pain. Pain has a very complex impact on the care of post partum mothers, includin Activity of Daily Living (ADL) is impaired. Non pharmacological management to reduce pain can be a progressive muscle relaxation technique. This study aims to determine the effect of progressive muscle relaxation techniques on pain at clients of post sectio caesarea in RSUD Kota Bandung. This study is a pre experimental study with one group pre test post test design approach. The number of sample in this study is 20 persons selected in purposive sampling technique. The applied instrument is Numeric Rating Scale (NRS) and work procedure of progressive muscle relaxation. The data is then analyzed by wilcoxon test. The study reveals that more than half of clients post operative sectio caesarea were on pain scale 6 before progressive muscle relaxation and almost half had pain scale 3 and 4 after progressive muscle relaxation. And acquired p value = 0.000, so it was concluded that there was influence of progressive muscle relaxation to pain scale to the clients of sectio caesarea. The results of this study it’s expected that progressive muscle relaxation technique can be used as reference for making SOP in the room and can be used as a non pharmacological intervention in pain management